The Nexus of Management Innovation, Performance Management, and Organizational Performance in the Pakistani Construction Industry - Aftab Junaid; Sarwar Huma; Abid Nabila; Ishaq Muhammad Ishtiaq; Kiran Alina; Aftab Fahad (Central European Management Journal, 2022)
Purpose: The construction industry in Pakistan faces a turbulent environment and multiple challenges to achieve its targets. In such situations, the interest in innovation grows, especially in management innovation, and the conviction about its significant role in boosting organizational performance gains researchers’ interest. Accordingly, this article examines the mediating role of performance management in the relationship between management innovation and organizational performance.